The Influence of Science Laboratory Management and Educational Facilities on Students’ Learning Interest at Public Junior High Schools in Paal 2 District, Manado City - Tamatompol, Marcela M.; Lumapow, Harol R.; Tambingon, Henny Nikolin; Mongdong, Romi J. (International Journal of Information Technology and Education, 2026)
Science laboratory management and the availability of educational facilities are critical factors in supporting effective science learning; however, suboptimal laboratory utilization and limited instructional resources remain persistent challenges in many Indonesian schools, particularly at the junior secondary level. This study aims to analyze the influence of science laboratory management and educational facilities on students’ learning interest at public junior high schools in Paal 2 District, Manado City. A quantitative ex post facto approach was employed, with data collected through validated structured questionnaires from 163 students selected using proportional random sampling from a population of 275 Grade VIII students. Data were analyzed using multiple linear regression with partial (t-test) and simultaneous (F-test) hypothesis testing. The results demonstrated that: (1) science laboratory management had a positive and significant influence on students’ learning interest (β = 0.452, t = 10.986, p < 0.001); (2) educational facilities had a positive and significant influence on students’ learning interest (β = 0.356, t = 5.071, p < 0.001); and (3) both variables simultaneously exerted a significant effect on learning interest (F = 78.235, p < 0.001), collectively explaining 49.4% of the variance (R² = 0.494). Laboratory management emerged as the stronger predictor (standardized β = 0.620) compared to educational facilities (standardized β = 0.286). These findings indicate that well-managed laboratories combined with adequate educational facilities are essential to fostering higher levels of student interest in science learning, implying that school administrators and policymakers should prioritize systematic laboratory management alongside facility improvement to enhance the quality of science education.